Effect of Intellectual Capital and Audit Opinion on Stock Prices: Empirical Study on Listed Infrastructure, Utilities and Transportation Companies - Nurmala, Putri; Adiwibowo, Akhmad Sigit; Sari, Afifah Kemala (Indonesian Journal Of Business And Economics, 2021)
This study aims to determine and obtain empirical evidence of the effect of intellectual capital and audit opinion on stock prices. This study uses quantitative research using descriptive methods. The population in this study includes infrastructure, utilities and transportation which are listed on the Indonesia Stock Exchange as many as 79 companies. The sampling technique used was purposive sampling by obtaining 60 data. The method of analysis using multiple linear regression models was processed and analyzed using the IBM Statistical Package for Social Sciences (SPSS) version 25 program. The results showed that intellectual capital and audit opinion had no effect on stock prices either simultaneously or partially. Keywords: Intellectual Capital, Audit Opinion and Stock Prices